STUDI PENGARUH SUHU DAN INTENSITAS RADIASI MATAHARI TERHADAP PERKEMBANGAN PENYAKIT PATIK PADA TEMBAKAU - Tantawi, Ahmad Rafiqi; Hadisutrisno, Bambang; Semangun, Haryono; Hartana, I; Lisnawita, Lisnawita (Jurnal Agroteknos, 2013)
The Study on Contribution of Temperature and Solar Radiation Intensity to Frogeye Disease Development on Tobacco. Tobacco is an important plant in Indonesia, due to its contribution to Indonesian economic and employment opportunity. One of the limiting factors in tobacco production is frogeye leaf spot, a fungal disease caused by  Cercospora nicotianae Ell. et Ev. Epidemic of this disease was supposed to have a close relationship with weather aspects, such as wind velocity, temperature, solar radiation intensity and relative humidity.. The experiment carried out at Mycology Laboratory, Study Program of Plant Pest and Disease, Faculty of Agriculture, UGM and two tobacco plantations in Jember a nd Klaten to study contribution of temperature and solar radiation intensity to frogeye disease development on tobacco. The results showed that frogeye disease development was support by weather elements. i.e. temperature, but solar radiation intensity is not important factor to disease development. Key words: tobacco, temperature, solar radiation intensity, frogeye disease development